New Amphiphilic Neamine Derivatives Active against Resistant Pseudomonas aeruginosa and Their Interactions with Lipopolysaccharides - Sautrey, Guillaume (American Society for Microbiology, 2014)
The development of novel antimicrobial agents is urgently required to curb the widespread emergence of multidrug-resistant bacteria like colistin-resistant Pseudomonas aeruginosa. We previously synthesized a series of amphiphilic neamine derivatives active against bacterial membranes, among which 3′,6-di-O-[(2″-naphthyl)propyl]neamine (3′,6-di2NP), 3′,6-di-O-[(2″-naphthyl)butyl]neamine (3′,6-di2NB), and 3′,6-di-O-nonylneamine (3′,6-diNn) showed high levels of activity and low levels of cytotoxicity (L. Zimmermann et al., J. Med. Chem. 56:7691–7705, 2013). We have now further characterized the activity of these derivatives against colistin-resistant P. aeruginosa and studied their mode of action; specifically, we characterized their ability to interact with lipopolysaccharide (LPS) and to alter the bacterial outer membrane (OM). The three amphiphilic neamine derivatives were active against clinical colistin-resistant strains (MICs, about 2 to 8 μg/ml), The most active one (3′,6-diNn) was bactericidal at its MIC and inhibited biofilm formation at 2-fold its MIC. They cooperatively bound to LPSs, increasing the outer membrane permeability. Grafting long and linear alkyl chains (nonyl) optimized binding to LPS and outer membrane permeabilization. The effects of amphiphilic neamine derivatives on LPS micelles suggest changes in the cross-bridging of lipopolysaccharides and disordering in the hydrophobic core of the micelles. The molecular shape of the 3′,6-dialkyl neamine derivatives induced by the nature of the grafted hydrophobic moieties (naphthylalkyl instead of alkyl) and the flexibility of the hydrophobic moiety are critical for their fluidifying effect and their ability to displace cations bridging LPS. Results from this work could be exploited for the development of new amphiphilic neamine derivatives active against colistin-resistant P. aeruginosa.